Factors affecting the co-movement of prices between peninsular Malaysia and Sabah : a focus on cabotage policy - Siti Marsila binti Mhd. Ruslan (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2018)
The issue of price disparity between Peninsular Malaysia and Sabah has always been an important topic of debate for a long time. Different stakeholders pinpoint different causes of this issue. The objective of this study, therefore, is to analyse the extent of integration between Peninsular Malaysia and Sabah by observing the co-movement of prices between those two markets, paying particular attention on the liberalisation of the cabotage policy in 2009 as the main driving factor. For this purpose, this study utilised the disaggregated monthly price data (consumer price index) for nine categories of goods and services in Peninsular Malaysia and Sabah from year 2004 to 2015, applying several empirical tests to determine whether any structural break(s) occurred within the period of the study (with the year 2009 as the reference). The stationarity of data is first being tested using the classical unit root test including ADF, PP and KPSS; and the unit root test with the break of Zivot and Andrews (ZA) and Perron test. The findings show different periods of structural break for each unit roots that have structural break(s), with most outcome of the unit root test showing breaks occurring between 2008 and 2010. However, the “furnishings, household equipment and routine household maintenance” and “housing, water, electricity, gas and other fuels” groups show the breaks occurring from 2012 to 2014. Consequently, this study does not show a stable long-run term relationship and co-movement of price between consumer price indexes (CPIs) for most groups, which indicates that the variables are not cointegrated in the Johansen Cointegration Test. Nevertheless, the Gregory and Hansen test shows that there is some form of cointegration with structural break(s) especially in 2008, albeit only for a few groups. This further cements that it is rather “inconsequential” to relate the break of CPIs with the liberalisation of the cabotage policy in 2009. This may imply that other factors could have affected the co-movement of price between Peninsular Malaysia and Sabah. Overall, the price for both Peninsular Malaysia and Sabah were not fully co-moved with structural break; as well as it is not directly linked with the liberalisation of the cabotage policy in 2009. Despite the lack of quantitative evidence, many still believe that, it is the “cabotage effect” that is the primary driver of the price disparity between Peninsular Malaysia and Sabah. As such, it seems imperative to study the other possible factors that might have caused this issue, based on inputs from selected stakeholders, applying the force-field analysis. The proposed idea for the cabotage policy and its relation to the higher price was divided into “forces for change” and “forces against change”. Subsequently, a force-field analysis was developed based on the stakeholder impact analysis, through the summarised list of pros and cons on the issue of cabotage policy and the price disparity it is affecting. The participants included shipping providers, port authorities, the government and special interest group. The main outcome depicted from the force-field analysis was that the price disparity between Peninsular Malaysia and Sabah could not be attributed to the cabotage policy alone. Several arguments on this issue had emerged, with most points referring to the economic condition in Sabah, including (i) the poor condition of ports, (ii) trade imbalances, (iii) economic activities remained sluggish (iv) poor accessibility between the port and retailers, (v) insufficient infrastructure and technical facilities, and (vi) political sentiments.